KEBIJAKAN PRESIDEN UKRAINA VIKTOR YANUKOVYCH MENOLAK MENANDATANGANI EU - UKRAINE ASSOCIATION AGREEMENT DENGAN UNI EROPA TAHUN 2013 - Fadly, Muhammad; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes the policy of the President of Ukraine Viktor Yanukovych rejected the EU- Ukraine Association Agreement treaty at a summit of Eastern Partnership Summit in Vilnius, Lithuania on 29 November 2013. EU- Ukraine Association Agreement is a further form of cooperation between Ukraine with the EU which provide a variety of assistance to both sides, particularly to Ukraine in the face of crisis. In contrast, rejection and strengthening cooperation agreement with Russia that made Ukraine Viktor Yanukovych makes people do a large-scale demonstration and conditions in Ukraine is experiencing the worst crisis in the history of Ukraine. The policy of Ukraine rejected EU- Ukraine Association Agreement because of the influence of Russian power in the foreign policy of Ukraine. Russian power in the gas sector and trade makes Yanukovych change its policy direction with the European Union. Yanukovych under Russian pressure assumes that the Eurasian Customs Union is an alternative choice for Ukraine in finding a solution to the crisis. Viktor Yanukovych was eventually dismissed from the parliament Verkhovna Rada because it violated his authority and immediately turned into a suspect on one of the bloody demonstrations that occurred in Ukraine.Keywords : Foreign Policy, Crisis in Ukraine, Demonstration, European Union, Eurasian Customs Union.